Implementation Management of Guyup Rupa Exhibition 10 Semarang State University - Johan Sutarjo; Muhammad Jazuli; Eko Raharjo (Green Publisher Indonesia, 2025)
The management of the Guyup Rupa 10 Exhibition at Semarang State University faces challenges in organizing, implementing, and evaluating an art event that meets increasing expectations for quality and audience engagement. Despite its significance in fostering student creativity and public appreciation, structured studies on university-level exhibition management remain limited. This study aims to analyze the planning, execution, and evaluation of the Guyup Rupa 10 Exhibition while identifying supporting and inhibiting factors. Using a qualitative descriptive method, data were collected through literature studies and analyzed systematically. The results reveal that successful exhibition management relies on strong teamwork, institutional support, adequate facilities, effective promotion, and public involvement. Conversely, budget constraints, coordination issues, limited visitor participation, and insufficient resources hinder optimal implementation. The findings emphasize the importance of comprehensive project management strategies to enhance future exhibitions. This research provides practical insights for improving art exhibition management in academic contexts and contributes to the broader discourse on integrating educational, artistic, and community interests.